2011
DOI: 10.1016/j.micinf.2011.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus gattii: an emerging fungal pathogen infecting humans and animals

Abstract: Infectious fungi are among a broad group of microbial pathogens that has and continues to emerge concomitantly due to the global AIDS pandemic as well as an overall increase of patients with compromised immune systems. In addition, many pathogens have been emerging and reemerging, causing disease in both individuals who have an identifiable immune defect and those who do not. The fungal pathogen Cryptococcus gattii can infect individuals with and without an identifiable immune defect, with a broad geographic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
120
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 120 publications
(223 reference statements)
4
120
0
7
Order By: Relevance
“…C. neoformans var. grubii is responsible of almost all the infections in AIDS patients whilst C. gattii affects mainly apparently immunocompetent persons (6). Both C. neoformans and C. gattii invade essentially the cerebral parenchyma; however, C. gattii is more likely to produce pulmonary and cerebral masses (cryptococcomas) (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C. neoformans var. grubii is responsible of almost all the infections in AIDS patients whilst C. gattii affects mainly apparently immunocompetent persons (6). Both C. neoformans and C. gattii invade essentially the cerebral parenchyma; however, C. gattii is more likely to produce pulmonary and cerebral masses (cryptococcomas) (6).…”
mentioning
confidence: 99%
“…grubii is responsible of almost all the infections in AIDS patients whilst C. gattii affects mainly apparently immunocompetent persons (6). Both C. neoformans and C. gattii invade essentially the cerebral parenchyma; however, C. gattii is more likely to produce pulmonary and cerebral masses (cryptococcomas) (6). conditions, infections caused by the members of the C. neoformans complex have become important causes of morbid-mortality with approximately 5-10% of the patients with CD4+ lymphopenia developing cryptococcosis (7).…”
mentioning
confidence: 99%
“…70 The ability of C. neoformans and C. gattii to grow at host body temperature (37 C) is one of the virulence attributes that is controlled by the calcineurin signaling pathway. 40,43 In addition, calcineurin is also required for growth at alkaline pH, hyphal elongation during mating and monokaryotic fruiting.…”
Section: Candida Cryptococcus and Emerging Moldsmentioning
confidence: 99%
“…Recent evidence has suggested that unisexual reproduction and recombination play an important role in generating virulent strains of Cryptococcus and other eukaryotic pathogens, including both fungi and parasites (Jenni et al 1986;Gaunt et al 2003;Fraser et al 2005;Akopyants et al 2009;Byrnes et al 2010Byrnes et al , 2011Wendte et al 2010;Minot et al 2012;Inbar et al 2013;Voelz et al 2013;Billmyre et al 2014). We tested whether parental strains with mutations that compromise virulence are able to undergo unisexual reproduction to produce virulent progeny.…”
Section: Unisexual Reproduction Between Attenuated Strains Restores Tmentioning
confidence: 99%